2015
DOI: 10.3389/fbioe.2015.00089
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Ureteral Grafts: Preparation of Biocompatible Crosslinked Ureteral Scaffolds of Porcine Origin

Abstract: The surgical reconstruction of ureteric defects is often associated with post-operative complications and requires additional medical care. Decellularized ureters originating from porcine donors could represent an alternative therapy. Our aim was to investigate the possibility of manufacturing decellularized ureters, the characteristics of the extracellular matrix (ECM) and the biocompatibility of these grafts in vitro/in vivo after treatment with different crosslinking agents. To achieve these goals, native u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 54 publications
(125 reference statements)
0
29
0
1
Order By: Relevance
“…Additionally, it should be observed that the presence of active metalloproteinases may lead to the degradation of the ECM. 4 A number of chemicals that do not lead to cell removal, but are used to crosslink the collagen-rich material, are being considered, 125 the dominant ones being: glutaraldehyde, formaldehyde, polyepoxy compounds and polyurethane, asylum azide, carbodiimidecompounds, hexamethylene diisocyanate, tannic acid, tartaric acid, vitamin B2-induced UVA crosslinking, and genipin 63,91,[125][126][127][128][129][130][131][132] (Table IV). As it is often described, the procedure for processing the dermis can consist of a two-step method based on enzymatic digestion of cellular elements and then cross-linked structure of the extracellular matrix with glutaraldehyde in order to mask residual cellular structures.…”
Section: Chemical Decellularization Methodsmentioning
confidence: 99%
“…Additionally, it should be observed that the presence of active metalloproteinases may lead to the degradation of the ECM. 4 A number of chemicals that do not lead to cell removal, but are used to crosslink the collagen-rich material, are being considered, 125 the dominant ones being: glutaraldehyde, formaldehyde, polyepoxy compounds and polyurethane, asylum azide, carbodiimidecompounds, hexamethylene diisocyanate, tannic acid, tartaric acid, vitamin B2-induced UVA crosslinking, and genipin 63,91,[125][126][127][128][129][130][131][132] (Table IV). As it is often described, the procedure for processing the dermis can consist of a two-step method based on enzymatic digestion of cellular elements and then cross-linked structure of the extracellular matrix with glutaraldehyde in order to mask residual cellular structures.…”
Section: Chemical Decellularization Methodsmentioning
confidence: 99%
“…Scaffolds derived from decellularized matrix (from both allogeneic and xenogeneic sources) have been investigated as materials for regeneration in a range of tissues: heart valve, 24,25,51,52 nasal cartilage, 53 skeletal muscle, 26 gastrointestinal tract, 27,54 ureters, 28 liver, 55 and flexor tendons. 56 Both segmented and whole tissues can be decellularized.…”
Section: Decellularized Matrix As Scaffold For Tissue Regenerationmentioning
confidence: 99%
“…27 Conversely, carbodiimide cross-linked porcine ureteral scaffolds implanted in a subcutaneous rat model showed a macrophage phenotypic switch to the anti-inflammatory M2 phenotype. 28 Cross-linking with glutaraldehyde or genipin stimulated a pro-inflammatory M1 macrophage switch in vivo. 28 These data are consistent with glutaraldehyde cross-linking of decellularized bovine pericardium which resulted in limited attachment and survival of macrophage-like cells (U937) and increased release of pro-inflammatory cytokines (MMP-1).…”
Section: Decellularized Matrix As Scaffold For Tissue Regenerationmentioning
confidence: 99%
See 2 more Smart Citations